Waterproof and heat-insulating composite fabric for clothing and preparation method thereof

By pasting the fluff and heat insulation layer on the waterproof and heat insulation clothing, and using modified mullite fibers and silicone cavity structures to form a porous heat insulation layer, the thermal insulation effect of existing waterproof and heat insulation clothing in high temperature environments is solved. The poor problem significantly improves the heat insulation and high temperature resistance of the clothing, and enhances the safety of emergency repair personnel.

CN118493979BActive Publication Date: 2024-12-17DALIAN LIANGGE TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311173528.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2024-12-17
Estimated Expiration
2043-09-12

AI Technical Summary

Technical Problem

The existing waterproof and thermal insulation clothing fabric has average heat insulation effect in high-temperature environments, which leads to low efficiency of emergency repair personnel when working in high-temperature hot water, increasing the risk of accidents.

Method used

The composite fabric is prepared by sticking the fluff and insulation layer on the knitted fabric, and electrospinning and hot pressing technology, and the porous insulation layer is formed using modified mullite fibers and silicone cavity structures, combining protective materials to improve Waterproof and high temperature resistance.

Benefits of technology

It significantly improves the thermal insulation and high temperature resistance of waterproof and thermal insulation clothing, extends the working time of emergency repair personnel in high temperature environments, and reduces the risk of accidents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004444719070000121
    Figure BDA0004444719070000121
  • Figure BDA0004444719070000131
    Figure BDA0004444719070000131
Patent Text Reader

Abstract

The invention discloses a waterproof and heat-insulating composite fabric for clothing and a preparation method thereof. A fluff layer is pasted on one side of a knitted fabric, and a heat-insulating layer is pasted on a side away from the fluff layer. A protective material is electrostatically spun and hot-pressed on the surface of the heat-insulating layer to prepare the waterproof and heat-insulating composite fabric for clothing. A polyamic acid salt and a modified filler are blended to form an aerogel under low temperature conditions. Then, under high temperature conditions, the polyamic acid salt undergoes thermal imidization, and simultaneously, a benzoxazine structure on a molecular chain undergoes ring-opening polymerization to form a heat-insulating layer. The heat-insulating layer is a porous structure with a certain heat-insulating effect. The matrix of the modified filler is mullite, and the surface contains organic silicon cavities to further improve the heat-insulating effect. The protective material molecules contain organic silicon segments and a large number of benzene ring structures, which further improve the waterproof effect of the protective material and simultaneously improve the high temperature resistance of the protective material, thereby increasing the durability of the composite fabric.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of waterproof and heat-insulating materials, and in particular to a waterproof and heat-insulating composite fabric for clothing and a preparation method thereof. Background Art

[0002] With the development of human society, the advancement of science and technology, the rapid development of urbanization, the demand for urban heating load has increased dramatically, the heating density of centralized heating systems has become larger and larger, and the heating radius has become larger and larger. In order to ensure the safe operation of equipment and pipelines during the heating operation period, prevent casualties and the expansion of the scope of accidents, and restore heating in time, the principle of prevention is adopted. Emergency repair work needs to repair equipment and pipelines as soon as possible while ensuring the safety of emergency repair personnel. Therefore, the waterproof and heat-insulating clothing of emergency repair personnel should be able to maximize work efficiency and carry out emergency repairs in time while protecting the safety of emergency repair personnel. Existing heat-insulating clothing, due to material limitations, cannot ensure that emergency repair personnel can work in high-temperature hot water for a long time, which increases the emergency repair time and increases the possibility of expanding the scope of accidents. Summary of the invention

[0003] The purpose of the present invention is to provide a composite fabric for waterproof and heat-insulating clothing and a preparation method thereof, which solves the problem that the heat insulation and high temperature resistance effects of the current waterproof and heat-insulating clothing fabrics are average.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A method for preparing a waterproof and heat-insulating composite fabric for clothing, comprising the following steps:

[0006] A fleece layer is pasted on one side of the knitted fabric, and a heat-insulating layer is pasted on the side away from the fleece layer. The protective material is dissolved in DMF, and electrostatic spinning is performed on the surface of the heat-insulating layer at a voltage of 25-30 kV and hot-pressed at a temperature of 100-120°C for 1-2 minutes to obtain a waterproof and heat-insulating composite fabric for clothing.

[0007] The pasting is completed by PTFE membrane pasting, and the usage ratio of waterproof material and DMF is 3g:20mL.

[0008] Furthermore, the thermal insulation layer is made by the following steps:

[0009] Step A1: dispersing mullite fiber in ethanol, stirring and adding deionized water and KH560 at a speed of 150-200 r / min and a temperature of 50-60° C., reacting for 2-3 hours to obtain modified mullite, uniformly mixing deionized water, tetraethylammonium hydroxide and isopropanol, stirring and adding KH550 at a speed of 200-300 r / min and a temperature of 30-35° C., stirring for 4-6 hours, heating to 75-80° C., reacting for 15-20 hours, filtering and removing the filtrate, dispersing the substrate in toluene, adding modified mullite, reacting for 2-3 hours at a pH of 11-12, and obtaining a modified filler;

[0010] Step A2: mixing hydroquinone, polyformaldehyde, p-aminobenzoic acid and toluene uniformly, reacting for 10-15 hours at a speed of 150-200 r / min and a temperature of 110-120° C., adding alumina, continuing the reaction for 30-40 minutes, filtering to remove the filter residue, distilling the filtrate to remove toluene to obtain a modifier, mixing the modifier, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, DCC and DMF, reacting for 5-7 hours at a speed of 200-300 r / min and a temperature of 25-30° C. to obtain a modified monomer;

[0011] Step A3: mixing the modified monomer, 3,3,4,4-biphenyltetracarboxylic acid dianhydride and N,N-dimethylacetamide, stirring for 2-4 hours at a speed of 300-500 r / min and a temperature of 0-3° C., heating to 20-25° C., adding triethylamine, and continuing the reaction for 3-4 hours, adding the reaction product to acetone, standing for 2-3 hours, filtering and removing the filtrate to obtain a polyamic acid salt;

[0012] Step A4: Mix the polyamic acid salt, modified filler, triethylamine and deionized water evenly, freeze them at a temperature of -15°C for 20-25 hours, freeze them in a liquid nitrogen environment at -196°C for 10-15 minutes, and then dry them at a temperature of -15°C and a vacuum degree of 1-2Pa to obtain a pretreated aerogel. Keep the pretreated aerogel at a temperature of 100-120°C for 1-2 hours, heat it to 180-200°C, keep it for 1-1.5 hours, heat it to 230-250°C, and keep it for 30-40 minutes to obtain a thermal insulation layer.

[0013] Furthermore, the amount of KH560 described in step A1 is 3% of the mass of the mullite fiber, and the mass ratio of deionized water, tetraethylammonium hydroxide, isopropanol, KH550 and modified mullite is 10:0.21:32:40.25:3.

[0014] Furthermore, the molar ratio of hydroquinone, polyformaldehyde and p-aminobenzoic acid described in step A2 is 1:4:2, the amount of alumina used is 1-1.5% of the total mass of hydroquinone, polyformaldehyde and p-aminobenzoic acid, and the molar ratio of modifier, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and DCC is n:n+1:n+1, where n is a natural number greater than 0.

[0015] Furthermore, the molar ratio of the modified monomer, 3,3,4,4-biphenyltetracarboxylic dianhydride and triethylamine described in step A3 is 1:1.01:2.4.

[0016] Furthermore, the usage ratio of the polyamic acid salt, modified filler, triethylamine and deionized water in step A4 is 3g:0.5g:0.1g:100mL.

[0017] Furthermore, the protective material is prepared by the following steps:

[0018] Step B1: diphenyldichlorosilane and deionized water are mixed, stirred for 10-15 minutes at a speed of 200-300 r / min and a temperature of 60-70° C., concentrated sulfuric acid and tetramethyldivinyldisiloxane are added, reacted for 4-6 hours, and the pH is adjusted to neutral to obtain intermediate 1, intermediate 1, styrene and methyl acrylate are mixed uniformly, azobisisobutyronitrile is added at a speed of 150-200 r / min and a temperature of 60-70° C., reacted for 3-5 hours, and the pH is adjusted to be alkaline to obtain a modified resin;

[0019] Step B2: Add PVC resin to sodium hydroxide solution, stir for 3-5 hours at a speed of 150-200 r / min and a temperature of 100-105° C., filter and remove the filtrate, mix the substrate, cyclohexanone, modified resin and azobisisobutyronitrile, introduce nitrogen protection, stir for 7-9 hours at a speed of 200-300 r / min and a temperature of 75-80° C., precipitate with methanol, filter and remove the filtrate to obtain a protective material.

[0020] Furthermore, the amount ratio of diphenyldichlorosilane, deionized water and tetramethyldivinyldisiloxane described in step B1 is 2mmol:10mL:1mmol, the amount of concentrated sulfuric acid is 1-1.5% of the total mass of diphenyldichlorosilane and tetramethyldivinyldisiloxane, the mass ratio of intermediate 1, styrene and methyl acrylate is 5:3:2, and the amount of azobisisobutyronitrile is 0.1-0.3% of the total mass of intermediate 1, styrene and methyl acrylate.

[0021] Furthermore, the dosage ratio of the PVC resin, sodium hydroxide solution, cyclohexanone and modified resin in step B2 is 10:80:50:1, the dosage of azobisisobutyronitrile is 0.1-0.3% of the total mass of the PVC resin and the modified resin, the mass fraction of the sodium hydroxide solution is 10%, and the molecular weight of the PVC resin is 2000.

[0022] Beneficial effects of the present invention: A waterproof and heat-insulating composite fabric for clothing prepared by the present invention is characterized in that a fluff layer is attached to one side of the knitted fabric, and a heat-insulating layer is attached to the side away from the fluff layer, and a protective material is electrostatically spun and hot-pressed on the surface of the heat-insulating layer to obtain a waterproof and heat-insulating composite fabric for clothing; the heat-insulating layer is made of mullite fiber as a raw material and treated with KH560 to graft epoxy groups on the surface; KH550 is hydrolyzed and polymerized to form an amino cage-type silsesquioxane, which reacts with the modified mullite under alkaline conditions. The surface amino group and the epoxy group react to form a cage-type structure to cover the mullite, thereby obtaining a modified filler; hydroquinone, polyformaldehyde and p-aminobenzoic acid react to form a benzoxazine structure to obtain a modifier; the modifier is dehydrated and condensed with 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane under the action of DCC to form an amino-terminated modified monomer by controlling the dosage; the modified monomer is reacted with 3,3,4,4-biphenyltetracarboxylic dianhydride to obtain a modified monomer. A polyamic acid salt should be formed, and the polyamic acid salt and the modified filler are blended to form an aerogel under low temperature conditions. Under high temperature conditions, the polyamic acid salt undergoes thermal imidization, and at the same time, the benzoxazine structure on the molecular chain undergoes ring-opening polymerization to form a heat-insulating layer. The heat-insulating layer is a porous structure with a certain heat-insulating effect. The matrix of the modified filler is mullite, and the surface contains silicone cavities, which can further improve the heat-insulating effect. The protective material is first hydrolyzed with diphenyldichlorosilane as a raw material, and then polymerized with tetramethyldivinyldisiloxane under the action of concentrated sulfuric acid to obtain an intermediate 1. The intermediate 1, styrene and methyl acrylate are polymerized to form polyacrylate to obtain a modified resin. After the PVC resin is treated with sodium hydroxide, it is grafted with the modified resin to obtain a protective material. The protective material molecule contains silicone segments and a large number of benzene ring structures, which further improves the waterproof effect of the protective material and improves its own high temperature resistance, thereby increasing the durability of the composite fabric. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] A method for preparing a waterproof and heat-insulating composite fabric for clothing, comprising the following steps:

[0026] A fleece layer is pasted on one side of the knitted fabric, and a heat-insulating layer is pasted on the side away from the fleece layer. The protective material is dissolved in DMF, and electrospun on the surface of the heat-insulating layer at a voltage of 25 kV and hot-pressed at a temperature of 100°C for 1 minute to obtain a waterproof and heat-insulating composite fabric for clothing.

[0027] The pasting is completed by PTFE membrane pasting, and the usage ratio of waterproof material and DMF is 3g:20mL.

[0028] The thermal insulation layer is made by the following steps:

[0029] Step A1: Disperse mullite fiber in ethanol, stir and add deionized water and KH560 at a speed of 150 r / min and a temperature of 50° C., and react for 2 hours to obtain modified mullite; mix deionized water, tetraethylammonium hydroxide and isopropanol evenly, stir and add KH550 at a speed of 200 r / min and a temperature of 30° C., stir for 4 hours, heat to 75° C., react for 15 hours, filter and remove the filtrate, disperse the substrate in toluene, add modified mullite, and react for 2 hours at a pH of 11 to obtain a modified filler;

[0030] Step A2: mixing hydroquinone, polyformaldehyde, p-aminobenzoic acid and toluene uniformly, reacting at a speed of 150 r / min and a temperature of 110° C. for 10 h, adding alumina, continuing the reaction for 30 min, filtering to remove the filter residue, distilling the filtrate to remove toluene to obtain a modifier, mixing the modifier, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, DCC and DMF, reacting at a speed of 200 r / min and a temperature of 25° C. for 5 h to obtain a modified monomer;

[0031] Step A3: Mix the modified monomer, 3,3,4,4-biphenyltetracarboxylic acid dianhydride and N,N-dimethylacetamide, stir for 2 hours at a speed of 300 r / min and a temperature of 0°C, heat to 20°C, add triethylamine, continue to react for 3 hours, add the reaction product into acetone, let stand for 2 hours, filter and remove the filtrate to obtain a polyamic acid salt;

[0032] Step A4: Mix the polyamic acid salt, modified filler, triethylamine and deionized water evenly, freeze them at a temperature of -15°C for 20 hours, freeze them in a liquid nitrogen environment at -196°C for 10 minutes, and then dry them at a temperature of -15°C and a vacuum degree of 1Pa to obtain a pretreated aerogel. Keep the pretreated aerogel at a temperature of 100°C for 1 hour, heat it to 180°C, keep it for 1 hour, heat it to 230°C, and keep it for 30 minutes to obtain a thermal insulation layer.

[0033] The amount of KH560 used in step A1 is 3% of the mass of the mullite fiber, and the mass ratio of deionized water, tetraethylammonium hydroxide, isopropanol, KH550 and modified mullite is 10:0.21:32:40.25:3.

[0034] The molar ratio of hydroquinone, polyformaldehyde and p-aminobenzoic acid described in step A2 is 1:4:2, the amount of alumina used is 1% of the total mass of hydroquinone, polyformaldehyde and p-aminobenzoic acid, and the molar ratio of modifier, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and DCC is 1:2:2.

[0035] The molar ratio of the modified monomer, 3,3,4,4-biphenyltetracarboxylic dianhydride and triethylamine in step A3 is 1:1.01:2.4.

[0036] The usage ratio of the polyamic acid salt, modified filler, triethylamine and deionized water described in step A4 is 3g:0.5g:0.1g:100mL.

[0037] The protective material is made by the following steps:

[0038] Step B1: diphenyldichlorosilane and deionized water were mixed, stirred for 10 min at a speed of 200 r / min and a temperature of 60° C., concentrated sulfuric acid and tetramethyldivinyldisiloxane were added, reacted for 4 h, and the pH was adjusted to neutral to obtain intermediate 1. Intermediate 1, styrene and methyl acrylate were mixed uniformly, azobisisobutyronitrile was added at a speed of 150 r / min and a temperature of 60° C., reacted for 3 h, and the pH was adjusted to be alkaline to obtain a modified resin;

[0039] Step B2: Add PVC resin to sodium hydroxide solution, stir for 3 hours at a speed of 150 r / min and a temperature of 100°C, filter and remove the filtrate, mix the substrate, cyclohexanone, modified resin and azobisisobutyronitrile, introduce nitrogen protection, stir for 7 hours at a speed of 200 r / min and a temperature of 75°C, precipitate with methanol, filter and remove the filtrate to obtain a protective material.

[0040] The amount ratio of diphenyldichlorosilane, deionized water and tetramethyldivinyldisiloxane described in step B1 is 2mmol:10mL:1mmol, the amount of concentrated sulfuric acid is 1% of the total mass of diphenyldichlorosilane and tetramethyldivinyldisiloxane, the mass ratio of intermediate 1, styrene and methyl acrylate is 5:3:2, and the amount of azobisisobutyronitrile is 0.1% of the total mass of intermediate 1, styrene and methyl acrylate.

[0041] The dosage ratio of the PVC resin, sodium hydroxide solution, cyclohexanone and modified resin described in step B2 is 10:80:50:1, the dosage of azobisisobutyronitrile is 0.1% of the total mass of the PVC resin and the modified resin, the mass fraction of the sodium hydroxide solution is 10%, and the molecular weight of the PVC resin is 2000.

[0042] Example 2

[0043] A method for preparing a waterproof and heat-insulating composite fabric for clothing, comprising the following steps:

[0044] A fleece layer is pasted on one side of the knitted fabric, and a heat-insulating layer is pasted on the side away from the fleece layer. The protective material is dissolved in DMF, and electrospun on the surface of the heat-insulating layer at a voltage of 28 kV and hot-pressed at a temperature of 110°C for 1.5 minutes to obtain a waterproof and heat-insulating composite fabric for clothing.

[0045] The pasting is completed by PTFE membrane pasting, and the usage ratio of waterproof material and DMF is 3g:20mL.

[0046] The thermal insulation layer is made by the following steps:

[0047] Step A1: Disperse mullite fiber in ethanol, stir and add deionized water and KH560 at a speed of 150 r / min and a temperature of 55° C., and react for 2.5 hours to obtain modified mullite; mix deionized water, tetraethylammonium hydroxide and isopropanol evenly, stir and add KH550 at a speed of 200 r / min and a temperature of 35° C., stir for 5 hours, heat to 78° C., react for 18 hours, filter and remove the filtrate, disperse the substrate in toluene, add modified mullite, and react for 2.5 hours at a pH of 11 to obtain a modified filler;

[0048] Step A2: mixing hydroquinone, polyformaldehyde, p-aminobenzoic acid and toluene uniformly, reacting for 15 hours at a speed of 150 r / min and a temperature of 115° C., adding alumina, continuing the reaction for 35 minutes, filtering to remove the filter residue, distilling the filtrate to remove toluene, and preparing a modifier; mixing the modifier, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, DCC and DMF, and reacting for 6 hours at a speed of 200 r / min and a temperature of 28° C. to prepare a modified monomer;

[0049] Step A3: The modified monomer, 3,3,4,4-biphenyltetracarboxylic acid dianhydride and N,N-dimethylacetamide were mixed, stirred for 3 hours at a speed of 500 r / min and a temperature of 0°C, heated to 23°C, triethylamine was added, and the reaction was continued for 3.5 hours. The reaction product was added to acetone, allowed to stand for 2 hours, and the filtrate was removed by filtering to obtain a polyamic acid salt;

[0050] Step A4: Mix the polyamic acid salt, modified filler, triethylamine and deionized water evenly, freeze them at a temperature of -15°C for 25 hours, freeze them in a liquid nitrogen environment at -196°C for 15 minutes, and then dry them at a temperature of -15°C and a vacuum degree of 1.5 Pa to obtain a pretreated aerogel. Keep the pretreated aerogel at a temperature of 110°C for 1.5 hours, heat it to 190°C, keep it for 1.5 hours, heat it to 240°C, and keep it for 35 minutes to obtain a thermal insulation layer.

[0051] The amount of KH560 used in step A1 is 3% of the mass of the mullite fiber, and the mass ratio of deionized water, tetraethylammonium hydroxide, isopropanol, KH550 and modified mullite is 10:0.21:32:40.25:3.

[0052] The molar ratio of hydroquinone, polyformaldehyde and p-aminobenzoic acid described in step A2 is 1:4:2, the amount of alumina used is 1.5% of the total mass of hydroquinone, polyformaldehyde and p-aminobenzoic acid, and the molar ratio of modifier, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and DCC is 2:3:3.

[0053] The molar ratio of the modified monomer, 3,3,4,4-biphenyltetracarboxylic dianhydride and triethylamine in step A3 is 1:1.01:2.4.

[0054] The usage ratio of the polyamic acid salt, modified filler, triethylamine and deionized water described in step A4 is 3g:0.5g:0.1g:100mL.

[0055] The protective material is made by the following steps:

[0056] Step B1: diphenyldichlorosilane and deionized water were mixed, stirred for 13 minutes at a speed of 300 r / min and a temperature of 65° C., concentrated sulfuric acid and tetramethyldivinyldisiloxane were added, reacted for 5 hours, and the pH was adjusted to neutral to obtain intermediate 1. Intermediate 1, styrene and methyl acrylate were mixed uniformly, azobisisobutyronitrile was added at a speed of 150 r / min and a temperature of 65° C., and the reaction was carried out for 4 hours. The pH value was adjusted to be alkaline to obtain a modified resin;

[0057] Step B2: Add PVC resin to sodium hydroxide solution, stir for 4 hours at a speed of 150 r / min and a temperature of 105° C., filter and remove the filtrate, mix the substrate, cyclohexanone, modified resin and azobisisobutyronitrile, introduce nitrogen protection, stir for 8 hours at a speed of 200 r / min and a temperature of 78° C., precipitate with methanol, filter and remove the filtrate to obtain a protective material.

[0058] The amount ratio of diphenyldichlorosilane, deionized water and tetramethyldivinyldisiloxane described in step B1 is 2mmol:10mL:1mmol, the amount of concentrated sulfuric acid is 1.5% of the total mass of diphenyldichlorosilane and tetramethyldivinyldisiloxane, the mass ratio of intermediate 1, styrene and methyl acrylate is 5:3:2, and the amount of azobisisobutyronitrile is 0.2% of the total mass of intermediate 1, styrene and methyl acrylate.

[0059] The dosage ratio of the PVC resin, sodium hydroxide solution, cyclohexanone and modified resin described in step B2 is 10:80:50:1, the dosage of azobisisobutyronitrile is 0.2% of the total mass of the PVC resin and the modified resin, the mass fraction of the sodium hydroxide solution is 10%, and the molecular weight of the PVC resin is 2000.

[0060] Example 3

[0061] A method for preparing a waterproof and heat-insulating composite fabric for clothing, comprising the following steps:

[0062] A fleece layer is pasted on one side of the knitted fabric, and a heat-insulating layer is pasted on the side away from the fleece layer. The protective material is dissolved in DMF, and electrospun on the surface of the heat-insulating layer at a voltage of 30 kV and hot-pressed at a temperature of 120°C for 2 minutes to obtain a waterproof and heat-insulating composite fabric for clothing.

[0063] The pasting is completed by PTFE membrane pasting, and the usage ratio of waterproof material and DMF is 3g:20mL.

[0064] The thermal insulation layer is made by the following steps:

[0065] Step A1: Disperse mullite fiber in ethanol, stir and add deionized water and KH560 at a speed of 200 r / min and a temperature of 60°C, and react for 3 hours to obtain modified mullite; mix deionized water, tetraethylammonium hydroxide and isopropanol evenly, stir and add KH550 at a speed of 300 r / min and a temperature of 35°C, stir for 6 hours, heat to 80°C, react for 20 hours, filter and remove the filtrate, disperse the substrate in toluene, add modified mullite, and react for 3 hours at a pH of 12 to obtain a modified filler;

[0066] Step A2: mixing hydroquinone, polyformaldehyde, p-aminobenzoic acid and toluene uniformly, reacting for 15 hours at a speed of 200 r / min and a temperature of 120° C., adding alumina, continuing the reaction for 40 minutes, filtering to remove the filter residue, distilling the filtrate to remove toluene, and preparing a modifier; mixing the modifier, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, DCC and DMF, and reacting for 7 hours at a speed of 300 r / min and a temperature of 30° C. to prepare a modified monomer;

[0067] Step A3: the modified monomer, 3,3,4,4-biphenyltetracarboxylic acid dianhydride and N,N-dimethylacetamide were mixed, stirred for 4 hours at a speed of 500 r / min and a temperature of 3° C., the temperature was raised to 25° C., triethylamine was added, and the reaction was continued for 4 hours. The reaction product was added to acetone, allowed to stand for 3 hours, and the filtrate was removed by filtering to obtain a polyamic acid salt;

[0068] Step A4: Mix the polyamic acid salt, modified filler, triethylamine and deionized water evenly, freeze them at a temperature of -15°C for 25 hours, freeze them in a liquid nitrogen environment at -196°C for 15 minutes, and then dry them at a temperature of -15°C and a vacuum degree of 2Pa to obtain a pretreated aerogel. Keep the pretreated aerogel at a temperature of 120°C for 2 hours, heat it to 200°C, keep it for 1.5 hours, heat it to 250°C, and keep it for 40 minutes to obtain a thermal insulation layer.

[0069] The amount of KH560 used in step A1 is 3% of the mass of the mullite fiber, and the mass ratio of deionized water, tetraethylammonium hydroxide, isopropanol, KH550 and modified mullite is 10:0.21:32:40.25:3.

[0070] The molar ratio of hydroquinone, polyformaldehyde and p-aminobenzoic acid described in step A2 is 1:4:2, the amount of alumina used is 1.5% of the total mass of hydroquinone, polyformaldehyde and p-aminobenzoic acid, and the molar ratio of modifier, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and DCC is 3:4:4.

[0071] The molar ratio of the modified monomer, 3,3,4,4-biphenyltetracarboxylic dianhydride and triethylamine in step A3 is 1:1.01:2.4.

[0072] The usage ratio of the polyamic acid salt, modified filler, triethylamine and deionized water described in step A4 is 3g:0.5g:0.1g:100mL.

[0073] The protective material is made by the following steps:

[0074] Step B1: diphenyldichlorosilane and deionized water were mixed, stirred for 15 minutes at a speed of 300 r / min and a temperature of 70°C, concentrated sulfuric acid and tetramethyldivinyldisiloxane were added, reacted for 6 hours, and the pH was adjusted to neutral to obtain intermediate 1. Intermediate 1, styrene and methyl acrylate were mixed uniformly, azobisisobutyronitrile was added at a speed of 200 r / min and a temperature of 70°C, and the reaction was carried out for 5 hours. The pH value was adjusted to be alkaline to obtain a modified resin;

[0075] Step B2: Add PVC resin to sodium hydroxide solution, stir for 5 hours at a speed of 200 r / min and a temperature of 105°C, filter and remove the filtrate, mix the substrate, cyclohexanone, modified resin and azobisisobutyronitrile, introduce nitrogen protection, stir for 9 hours at a speed of 300 r / min and a temperature of 80°C, precipitate with methanol, filter and remove the filtrate to obtain a protective material.

[0076] The amount ratio of diphenyldichlorosilane, deionized water and tetramethyldivinyldisiloxane described in step B1 is 2mmol:10mL:1mmol, the amount of concentrated sulfuric acid is 1.5% of the total mass of diphenyldichlorosilane and tetramethyldivinyldisiloxane, the mass ratio of intermediate 1, styrene and methyl acrylate is 5:3:2, and the amount of azobisisobutyronitrile is 0.3% of the total mass of intermediate 1, styrene and methyl acrylate.

[0077] The dosage ratio of the PVC resin, sodium hydroxide solution, cyclohexanone and modified resin described in step B2 is 10:80:50:1, the dosage of azobisisobutyronitrile is 0.3% of the total mass of the PVC resin and the modified resin, the mass fraction of the sodium hydroxide solution is 10%, and the molecular weight of the PVC resin is 2000.

[0078] Comparative Example 1

[0079] Compared with Example 1, this comparative example uses mullite fiber instead of modified filler, and the other steps are the same.

[0080] Comparative Example 2

[0081] Compared with Example 1, this comparative example uses 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane instead of the modified monomer, and the remaining steps are the same.

[0082] Comparative Example 3

[0083] Compared with Example 1, this comparative example does not add modified filler, and the remaining steps are the same.

[0084] Comparative Example 4

[0085] Compared with Example 1, this comparative example did not add intermediate 1, and the remaining steps were the same.

[0086] The thermal insulation layers prepared in Examples 1-3 and Comparative Examples 1-3 were made into 50mm×50mm×3mm specimens according to the standard of GB / T32064-2015. The test temperature was 25°C and the sampling time was 5 seconds. The thermal conductivity was tested. The protective materials prepared in Examples 1-3 and Comparative Example 4 were tested for tensile strength according to the standard of GB / T8804.3-2003. They were kept warm at 90°C for 200h and the tensile strength was tested again. The test results are shown in the following table.

[0087]

[0088]

[0089] It can be seen from the above table that this application has good high temperature resistance and heat insulation effects.

[0090] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a waterproof and heat-insulating composite fabric for clothing, characterized in that: Made by the following steps: A fleece layer is attached to one side of the knitted fabric, and a heat insulation layer is attached to the side away from the fleece layer, and a protective material is electrostatically spun and hot-pressed on the surface of the heat insulation layer to obtain a waterproof and heat-insulating composite fabric for clothing; The thermal insulation layer is made by the following steps: Step A1: dispersing mullite fiber in ethanol, stirring and adding deionized water and KH560 to react to obtain modified mullite, mixing deionized water, tetraethylammonium hydroxide and isopropanol and stirring, adding KH550, stirring, heating to react, filtering and removing the filtrate, dispersing the substrate in toluene, adding modified mullite to react to obtain a modified filler; Step A2: mixing hydroquinone, polyformaldehyde, p-aminobenzoic acid and toluene for reaction, adding alumina, continuing the reaction, filtering to remove the filter residue, distilling the filtrate to remove the toluene to obtain a modifier, mixing the modifier, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, DCC and DMF for reaction to obtain a modified monomer; Step A3: mixing and stirring the modified monomer, 3,3,4,4-biphenyltetracarboxylic acid dianhydride and N,N-dimethylacetamide, heating and adding triethylamine, continuing the reaction, adding the reaction product into acetone, standing for treatment, filtering and removing the filtrate, and obtaining a polyamic acid salt; Step A4: uniformly mixing polyamic acid salt, modified filler, triethylamine and deionized water, freezing and drying to obtain pretreated aerogel, and heating and insulating the pretreated aerogel to obtain a heat insulation layer; The protective material is made by the following steps: Step B1: After mixing and stirring diphenyldichlorosilane and deionized water, concentrated sulfuric acid and tetramethyldivinyldisiloxane are added, reacted, and the pH is adjusted to neutral to obtain intermediate 1, intermediate 1, styrene and methyl acrylate are evenly mixed, azobisisobutyronitrile is added, reacted, and the pH is adjusted to be alkaline to obtain a modified resin; Step B2: adding PVC resin to sodium hydroxide solution, stirring, filtering and removing the filtrate, mixing the substrate, cyclohexanone, modified resin and azobisisobutyronitrile, introducing nitrogen protection, stirring, precipitating with methanol, filtering and removing the filtrate, and obtaining a protective material.

2. The method for preparing a waterproof and heat-insulating composite fabric for clothing according to claim 1, characterized in that: The amount of KH560 used in step A1 is 3% of the mass of the mullite fiber, and the mass ratio of deionized water, tetraethylammonium hydroxide, isopropanol, KH550 and modified mullite is 10:0.21:32:40.25:

3.

3. The method for preparing a waterproof and heat-insulating composite fabric for clothing according to claim 1, characterized in that: The molar ratio of hydroquinone, paraformaldehyde and p-aminobenzoic acid described in step A2 is 1:4:2, the amount of alumina used is 1-1.5% of the total mass of hydroquinone, paraformaldehyde and p-aminobenzoic acid, and the molar ratio of the modifier, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and DCC is n:n+1:n+1, where n is a natural number greater than 0.

4. The method for preparing a waterproof and heat-insulating composite fabric for clothing according to claim 1, characterized in that: The molar ratio of the modified monomer, 3,3,4,4-biphenyltetracarboxylic dianhydride and triethylamine in step A3 is 1:1.01:2.

4.

5. The method for preparing a waterproof and heat-insulating composite fabric for clothing according to claim 1, characterized in that: The usage ratio of the polyamic acid salt, modified filler, triethylamine and deionized water described in step A4 is 3g:0.5g:0.1g:100mL.

6. The method for preparing a waterproof and heat-insulating composite fabric for clothing according to claim 1, characterized in that: The amount ratio of diphenyldichlorosilane, deionized water and tetramethyldivinyldisiloxane described in step B1 is 2mmol:10mL:1mmol, the amount of concentrated sulfuric acid is 1-1.5% of the total mass of diphenyldichlorosilane and tetramethyldivinyldisiloxane, the mass ratio of intermediate 1, styrene and methyl acrylate is 5:3:2, and the amount of azobisisobutyronitrile is 0.1-0.3% of the total mass of intermediate 1, styrene and methyl acrylate.

7. The method for preparing a waterproof and heat-insulating composite fabric for clothing according to claim 1, characterized in that: The usage ratio of the PVC resin, sodium hydroxide solution, cyclohexanone and modified resin in step B2 is 10:80:50:1, and the usage of azobisisobutyronitrile is 0.1-0.3% of the total mass of the PVC resin and the modified resin.

8. A waterproof and heat-insulating composite fabric for clothing, characterized by: Prepared according to any one of claims 1 to 7.